Designing touch-enabled electronic flight bags in SAR helicopter operations - Avsar, Huseyin; Fischer, Joel E.; Rodden, Tom (2016)
In order to benefit from potential reduced operational costs and crew workload airlines are increasingly interested in touchscreen-based Electronic Flight Bags (EFB). This paper focuses on the specific domain of Search and Rescue (SAR) Helicopters. A first set of results aiming to explore and understand potential benefits and challenges of an EFB in a SAR environment will be presented. A review of related work, operational observations and interviews with pilots were conducted to understand and specify the use context. Digital Human Modelling (DHM) software was used to determine physical constraints of an EFB in this type of flight deck. A scenario was developed which will be used in future to define features, content and functionality that a SAR pilot may wish to see in an EFB. Developed initial interface design guidelines are presented.